18-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography in the Management of Aggressive Non-Hodgkin's B-Cell Lymphoma. (11th March 2012) - Shelly, M. J.; McDermott, S.; O'Connor, O. J.; Blake, M. A.
Abstract : 18-Fluorodeoxyglucose (FDG-PET/CT) is an established imaging modality that has been proven to be of benefit in the management of aggressive B-cell non-Hodgkin's lymphoma, such as diffuse large B-cell lymphoma and advanced stage follicular lymphoma. The combination of anatomic and functional imaging afforded by FDG-PET/CT has led to superior sensitivity and specificity in the primary staging, restaging, and assessment of response to treatment of hematological malignancies when compared to FDG-PET and CT alone. The use of FDG-PET/CT for posttreatment surveillance imaging remains controversial, and further study is needed to ascertain whether this modality is cost effective and appropriate for use in this setting.